THE EFFECTS OF DIFFERENT PROCESSING METHOD TOWARD QUALITY OF SHRIMP (Acetes erythraeus) SAUSAGE - Wau, Edwinar R; Suparmi, Suparmi; Desmelati, Desmelati (Fakultas Perikanan dan Kelautan Universitas Riau, 2010)
This research was conducted in June-July of 2010 and aimed to find out thebest quality shrimp sausage that were treated differently (boiling and roasting).Parameters of measured were organoleptic test, proximate analysis and TPC analysis.Results shown that the roasting sausage provided the best visual characteristics,good taste, compact texture, typical grilled sausage aroma, lower water content,higher protein content and has the lowest total bacteria colonies. The grilled sausagecan be kept up to 20 days in refrigerator (50 C).